Quantitative proteomic analysis reveals the influence of plantaricin BM-1 on metabolic pathways and peptidoglycan synthesis in Escherichia coli K12 - Wang, Huan; Xie, Yuanhong; Zhang, Hanwei; Jin, Junhua; Zhang, Hongxing (PLOS ONE, 2020)
Plantaricin BM-1 is a class IIa bacteriocin with a strong bactericidal effect on gram-positive bacteria. Although plantaricin BM-1 also inhibits the growth of some gram-negative bacteria, including Escherichia coli, the mechanism is not clear. In this study, we used tandem mass tag-based quantitative proteomics analysis to examine the inhibitory mechanism of plantaricin BM-1 against E. coli K12, and evaluated the morphological effects by electron microscopy. The results demonstrated that plantaricin BM-1 inhibits the growth of E. coli K12 by bacteriostatic action, mainly acting on the surface of the cell wall, leading to its collapse. Proteomic analysis identified 976 differentially expressed proteins (>1.2-fold change, p < 0.05) under treatment with plantaricin BM-1, including 490 up-regulated proteins and 486 down-regulated proteins. These proteins were mainly involved in peptidoglycan synthesis and energy metabolism pathways, including amino acid, glyoxylate and dicarboxylate, ABC transporter, and quorum-sensing pathways. Specifically, plantaricin BM-1 treatment significantly improved peptidoglycan synthesis and enhanced the tricarboxylic acid cycle in E. coli K12, and altered the expression of cell membrane proteins. These results provide new insight into the inhibition mechanism of class IIa bacteriocins on gram-negative bacteria, which can lay the foundation for its broader use as an alternative to conventional antibiotics.